2014
DOI: 10.1149/2.005405jss
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Mechanism for Patterned Sapphire Substrates by Wet Etching

Abstract: Patterned sapphire substrate (PSS) was fabricated by wet etching solutions with different mixture ratios of H2SO4 to H3PO4 and different temperatures to investigate the fabrication mechanisms. It was found that the mixture ratio and temperature of the etching solutions affect the ratio of the pattern diameter to the pattern depth. In addition, the observed pattern shape was strongly affected by the mixture ratio. To discuss the reaction mechanisms of sapphire with H2SO4 and H3PO4 separately, we estimated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 23 publications
0
38
1
Order By: Relevance
“…However, to our surprise, AFM study on crystallographic and topographical evolution of PSS was only scarcely reported. 20,30 Therefore, it is promising that complementary SEM and AFM characterizations of PSS can overcome the shortcomings of two techniques and provide more reliable and accurate dimensional/profile information.…”
mentioning
confidence: 99%
“…However, to our surprise, AFM study on crystallographic and topographical evolution of PSS was only scarcely reported. 20,30 Therefore, it is promising that complementary SEM and AFM characterizations of PSS can overcome the shortcomings of two techniques and provide more reliable and accurate dimensional/profile information.…”
mentioning
confidence: 99%
“…23 The E a was only estimated for the diameter and depth of etched holes instead of crystallographic planes. However, this results in unrealistic low E a values-only 9.1 kJ/mol and 51.4 kJ/mol for the diameter of holes.…”
Section: Cpss Etched Inmentioning
confidence: 99%
“…28,31,32 Alunogens are insoluble in H 2 SO 4 and preferentially nucleate and grow on the reaction active sites (step edges and defects) of crystallographic planes. 23 At the same time, H 3 PO 4 in M5-1 can remove insoluble alunogens to expose the underlying fresh surface, thus enabling H 2 SO 4 and H 3 PO 4 to etch the exposed step-terrace structures of crystallographic planes. It is thus reasonable to propose that, for high Miller index planes, higher density of step-terrace structures (with more reaction active sites) may favor more abundant nucleation sites and thus smaller alunogen particles, leading to faster removal of alunogens and hence higher etching rate of sapphire; lower E a for these planes can thus 21,23 we can explain the finding that E a for c-plane in M5-1 (94.5 kJ/mol) is slightly less than that in H 3 PO 4 (96.9 kJ/mol).…”
Section: Cpss Etched Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction products from H 3 PO 4 and sapphire are soluble, while those from H 2 SO 4 and sapphire are insoluble. 4,9,10 Aota et al thought that the step flow reaction with or without the impurities might control the pattern shape of the PSS. 9 The insoluble products would block the reaction step, which led to reduction in the rate of the step flow reaction.…”
Section: Introductionmentioning
confidence: 99%